The Impact of Digital Marketing and Electronic Word of Mouth on Impulse Buying of Adidas Running Shoes in Surabaya - Hikam, Syahrul; Supriyono (International Journal of Economics (IJEC), 2024)
The fashion industry, primarily running shoes, has become a significant market phenomenon in modern society. From 2019 to 2023, Nike and Adidas were the dominant competitors in the Indonesian sports footwear industry. However, Adidas experienced a decline in its market share beginning in 2021. The purpose of this study is to examine The Impact of Digital Marketing and Electronic Word of Mouth (e-WoM) on the impulse buying of Adidas running shoes. The research employs a quantitative research strategy that utilizes a survey methodology. A total of 100 participants were selected through purposive sampling methods. The study sample is composed of adult residents of Surabaya, aged 17 years and older, who have previously acquired information about Adidas products and have engaged in impetuous purchasing. A five-point Likert scale questionnaire was employed to capture primary data, which was subsequently analyzed using Structural Equation Model (SEM) PLS. The results suggest that impulsive purchasing is significantly influenced by both digital marketing and e-WoM, with e-WoM exhibiting a more significant impact.